Neural correlates of high-risk behavior tendencies and impulsivity in an emotional Go/NoGo fMRI task - Brown, Matthew R. G.; Benoit, James R. A.; Juhás, Michal; Lebel, R. M.; MacKay, Marnie; Dametto, Ericson; Silverstone, Peter H.; Dolcos, Florin; Dursun, Serdar M.; Greenshaw, Andrew J. (Frontiers in Systems Neuroscience, 2015)
Improved neuroscientific understanding of high-risk behaviours such as alcohol binging, drug use, and unsafe sex will lead to therapeutic advances for high-risk groups. High-risk behaviour often occurs in an emotionally-charged context, and behavioural inhibition and emotion regulation play important roles in risk-related decision making. High impulsivity is an important potential contributor to high-risk behaviour tendencies. We explored the relationships between high-risk behaviour tendencies, impulsivity, and fMRI brain activations in an emotional Go/NoGo task. This task presented emotional distractor pictures (aversive vs. neutral) simultaneously with Go/NoGo stimuli (square vs. circle) that required a button press or withholding of the press, respectively. Participants' risk behaviour tendencies were assessed with the Cognitive Appraisal of Risky Events (CARE) scale. The Barratt Impulsivity Scale 11 (BIS) was used to assess participant impulsivity. Individuals with higher CARE risk scores exhibited reduced activation related to response inhibition (NoGo-Go) in right orbital frontal cortex (OFC) and ventromedial prefrontal cortex. These regions did not show a significant relationship with impulsivity scores. Conversely, more impulsive individuals showed reduced emotion-related activity (aversive-neutral distractors) in dorsomedial prefrontal cortex, perigenual anterior cingulate cortex, and right posterior OFC. There were distinct neural correlates of high-risk behaviour tendency and impulsivity in terms of brain activity in the emotional Go/NoGo task. This dissociation supports the conception of high-risk behaviour tendency as a distinct construct from that of impulsivity. Our results suggest that treatment for high-risk behaviour may be more effective with a nuanced approach that does not conflate high impulsivity necessarily with high-risk behaviour tendencies.